The Influence of Performance Expectancy, Facility Conditions, Social Influence, Innovation, Technological Security and Hedonistic Motivation on the Adoption of E-Wallets with Behavioural Intent as a Mediating Variable - Andre Efendi; Vidyarini Dwita (International Journal Labs, 2026)
This study was conducted with the aim of analyzing and determining the influence of performance expectancy, facility conditions, social influence, innovation, technological security and hedonistic motivation on the adoption of e-wallets with behavioral intentions as a mediating variable (in Gebi Jaya Wholesale Customers). The type of research conducted is quantitative research. The population in this study is customers who have made payments using E-Wallet at Toko Geby Jaya with a sample of 130 people or respondents. In this study, the analysis was carried out using SEM PLS with SmartPLS Software 4.0. The results of this study show that (1) performance expectancy does not have a significant effect on e-wallet adoption, (2) facility conditions have a significant effect on e-wallet adoption, (3) social influence does not have a significant effect on e-wallet adoption, (4) innovation does not have a significant effect on e-wallet adoption, (5) technological security has a significant effect on e-wallet adoption, (6) hedonistic motivation does not have a significant effect on e-wallet adoption, (7) Behavioral intentions have a significant effect on e-wallet adoption, (8) Performance expectancy does not have a significant effect on e-wallet adoption with behavioral intent as a mediation variable, (9) facility conditions have a significant effect on e-wallet adoption with behavioral intent as a mediation variable, (10) social influence does not have a significant effect on e-wallet adoption with behavioral intent as a mediating variable, (11) innovation does not have a significant effect on adoption e-wallets with behavioral intent as a mediating variable, (12) technological security has a significant effect on the adoption of e-wallets with behavioral intent as a mediation variable, (13) hedonistic motivation does not have a significant effect on the adoption of e-wallets with behavioral intent as a mediating variable.